A Case of Lymphocytic Infundibulo-neurohypophysitis Exhibiting Spontaneous Regression. Issue 2 (27th February 2023) - Hasebe, Masashi; Shibue, Kimitaka; Honjo, Sachiko; Hamasaki, Akihiro
Abstract: Lymphocytic infundibulo-neurohypophysitis (LINH) is a rare autoimmune inflammatory process that selectively affects the neurohypophysis and the pituitary stalk, typically presenting with central diabetes insipidus (CDI). LINH is considered underdiagnosed because the definitive diagnosis requires invasive pituitary surgery with a high risk of complications. We present a case of CDI resulting from LINH, which was treated with conservative management, eschewing both glucocorticoid treatment and pituitary surgery. At presentation, the hormonal assessment indicated the presence of CDI without anterior pituitary dysfunction. Magnetic resonance imaging revealed stalk thickening without a posterior pituitary bright spot, and anti-rabphilin-3A antibodies were positive in serum. Collectively, we made a diagnosis of LINH. Considering that the patient did not exhibit any symptoms of mass effect, we chose conservative treatment with desmopressin acetate. One year later, the stalk thickening regressed spontaneously without surgical or glucocorticoid treatment, although the posterior pituitary bright spot remained absent, and CDI did not improve. The inflammatory process of LINH is mostly self-limited and recovers spontaneously, whereas life-long desmopressin treatment may be required because of pituitary stalk fibrosis and atrophy. Our case highlights the importance of noninvasive diagnosis and careful follow-up in preventing unnecessary interventions for patients with LINH.